The Reliable Poem: A 17th-century Hindi Poet in his Words - Piotr Borek (Ksiegarnia Akademicka Publishing, 2021)
The article is devoted to the 17th-century poet Bhushan, author of Śivarājabhūṣaṇa, a rītigranth most probably commissioned by the emerging Maratha ruler Shivaji Bhonsle. The existing histories of Hindi literature provide multiple accounts on the life of the poet, often calling them the hearsay tradition. Although many of them are drawn from a Maratha chronicle (bakhar), a proper study on the source of such accounts is still lacking. One more source that gives a chance to retrieve the curricula of Bhushan is Śivarājabhūṣaṇa, the only homogenic text that is attributed to the poet. The manuscripts and the editions of this text, especially the stanzas referring to the poet himself, do not show significant changes or interpolations. It allows us to treat it as a relatively reliable source, and therefore the treatise can serve as a basis for the reconstruction of the poet’s life and the circumstances of its composition. All portions of the text which refer to his biography are presented in order to provide complete data that can be drawn out of the internal evidence.